Janus Kinase (JAK) Inhibitors in Rheumatoid Arthritis - Vishal R. Tandon; Annil Mahajan (Dr. Annil Mahajan, 2022)
Janus kinase (JAK) and signal transducer and activator of transcription (STAT) signalling has been established to have pathophysiological role in multiple disease states, such as myeloproliferative neoplasms, rheumatoid arthritis, inflammatory bowel disease and multiple immune-driven dermatological diseases etc. JAK inhibitors are low-molecular-weight compounds, which exert anti-rheumatic effects by suppressing the action of JAK, an intracellular tyrosine kinase. JAK inhibitors are useful mainly in a variety of cases, including patients who inadequately responded to treatment with methotrexate and/or DMARDs.